Reversibility of a High-Grade Atrioventricular Block Treated Homeopathically - Jeggels, Herman John Daniel (Homœopathic Links, 2021)
Background A 61-year-old female patient requested a homeopathic therapy as an alternative to a pacemaker for a non-acute myocardial infarction, high-grade atrioventricular node block (HG-AVNB) with a narrow QRS complex.Methods Homeopathic Digitalis purpurea (Digitalis) was employed to accelerate the patient's heart rate.Results Digitalis caused within 3 days a pulse rate of about 90 beats per minute (bpm) which is represented on the electrocardiogram (ECG) by an accelerated junctional rhythm (AJR).The AJR compelled seeking a medicine to reduce its rate. Homeopathic Arsenicum album (Arsenicum) reduced its rate and also seemed to have assisted in the unanticipated recovery of the atrioventricular node (AVN).Conclusions This case report represents, an ECG documented case of a medical treatment modality which could be an alternative to pacemakers for patients with a HG-AVNB with a narrow QRS complex. Digitalis has been safe and effective during its 3 and a half year employment.
Keywords: high-grade atrioventricular node block; homeopathic Digitalis purpurea; accelerated junctional rhythm; case report; homeopathy